C646 Protects Against DSS-Induced Colitis Model by Targeting NLRP3 Inflammasome - Xu, Xueming; Li, Jing; Long, Xiuyan; Tao, Sifan; Yu, Xiaoyu; Ruan, Xixian; Zhao, Kai; Tian, Li (Frontiers in Pharmacology, 2021)
Numerous pieces of evidence have identified that the NLRP3 inflammasome plays a pivotal role in the development and pathogenesis of colitis. Targeting the NLRP3 inflammasome represents a potential therapeutic treatment. Our previous studies have suggested that acetylation of NLRP3 is indispensable to NLRP3 inflammasome activation, and some acetyltransferase inhibitors could suppress the NLRP3 inflammasome activation. Here, we identified that C646, an inhibitor of histone acetyltransferase p300, exerts anti-inflammatory effects in DSS-induced colitis mice by targeting the NLRP3 inflammasome. Mechanistically, C646 not only inhibits NF-κB activation, leading to the decreased expression of pro-inflammatory cytokines (IL-1β, IL-6, and TNF-α) and NLRP3, but also suppresses the NLRP3 inflammasome assembly by disrupting the interaction between NLRP3 and ASC. In addition, C646 attenuated the LPS-induced acute systemic inflammation model. Thus, our results demonstrate the ability of C646 to suppress the NLRP3 inflammasome activity and its potential application in the treatment of inflammatory bowel disease.